The Negative and Positive Aspects of Employees’ Innovative Behavior: Role of Goals of Employees and Supervisors - Zhang, Ying; Zhang, Jian; Forest, Jacques; Chen, Chunxiao (Frontiers in Psychology, 2018)
We aim to examine the negative (relationship conflict) and positive (in-role job performance) outcomes of employees’ innovative behavior, and explored the moderation effect of employees’ goal content and supervisors’ achievement goal orientation in these relationships. The dData were collected from 218 employees and their immediate supervisors were collected in companies in China, and the results show that employees’ innovative behaviors are positively related to their relationship conflict and in-role job performance, and employees’ extrinsic goals and supervisors’ performance goal moderate these relationships. Specifically, employees’ innovative behaviors were significantly and positively related to relationship conflict when either employees have high extrinsic goals or supervisor have high performance goals or both; and when supervisor have low level of performance goals, employees’ innovative behaviors were significantly and positively related to their in-role job performance. We contribute in showing when there are positive and negative outcomes of employees’ innovative behaviors and document the effect of moderating factors that may strengthen these benefits and lower the conflicts.